Proteinuria in Asymptomatic Siblings of Children with Steroid Resistant Nephrotic Syndrome: A Screening Using Urinary Dipstick - Zubair, Aasia; Hina Fatima; Madiha Aziz; Khatri, Sabeeta; Ali, Irshad; Seema Hashmi (Journal of the Pakistan Medical Association, 2022)
Objective: To screen asymptomatic siblings of steroid-resistant nephrotic syndrome patients for proteinuria using the urinary dipstick method to determine the involvement of siblings in the familial and likely genetic cause of the steroid-resistant nephrotic syndrome. Methods: This cross-sectional study was performed at the outpatient department of Sindh Institute of Urology and Transplantation (SIUT) from May to July 2021. Results: Out of 104 patients with steroid-resistant nephrotic syndrome, siblings of 66 patients were enrolled. Mean age of primary patients with steroid resistant nephrotic syndrome was 8.7±4.3 years. Most common histopathological diagnosis was focal segmental glomerulosclerosis in 25 (37.9%) children followed by minimal change disease in 17(25.8%) of them. The majority, 48 (72.7%) patients were on immunosuppressive treatment, while 4 (6.1%) had progressed to chronic kidney disease (CKD). A total of 178 siblings were recruited in the study. There were 99(55.6%) boys and 79(44.4%) girls. Their mean age was 10.67±6.2 years. Consanguinity was high in our study population i.e. 56(84%) families. Positive proteinuria on dipstick was detected in only 5(7.5%) enrolled SRNS families. One family refused further testing. Two of the five affected siblings had nephrotic range proteinuria. Renal biopsy of one of them showed membranous nephropathy while the second showed mesangiocapillary glomerulonephritis. Both had normal renal functions. Conclusion: The frequency of proteinuria in asymptomatic siblings of children with steroid-resistant syndrome is low in our population despite a high prevalence of consanguineous marriages. Hence, familial involvement of nephrotic syndrome is low and further genetic testing for monogenic causes is required in steroid-resistant nephrotic syndrome cases. Keywords: steroid-resistant, nephrotic, syndrome, proteinuria.